2012
DOI: 10.4049/jimmunol.1102674
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Trem-like Transcript-1 Regulates Leukocyte Activation and Controls Microbial Sepsis

Abstract: The triggering receptor expressed on myeloid cells (TREM)-1 plays a crucial role during the onset of sepsis by amplifying the host immune response. The TREM-like transcript-1 (TLT-1) belongs to the TREM family, is selectively expressed on activated platelets, and is known to facilitate platelet aggregation through binding to fibrinogen. In this study, we show that a soluble form of TLT-1 is implicated in the regulation of inflammation during sepsis by dampening leukocyte activation and modulating platelet-neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 32 publications
3
96
1
Order By: Relevance
“…Considering that inhibition of Trem-1 only occurs during the first 5 days after MI (the LR12 half-life is short), 8 we thus speculate that the initial modulation of the inflammatory response must be responsible for this late-onset ventricular function improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that inhibition of Trem-1 only occurs during the first 5 days after MI (the LR12 half-life is short), 8 we thus speculate that the initial modulation of the inflammatory response must be responsible for this late-onset ventricular function improvement.…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 activation can be limited by the use of an inhibitory peptide (LR12) that we previously reported to have protective effects during septic shock. [8][9][10] On the opposite, TREM-1 can be engaged by an agonistic mAb (Trem-1 mAb). 6 Although mAb administration decreased survival, LR12 treatment was associated with a reduced death rate, not different to the one observed in Trem-1 Figure 1F).…”
Section: Trem-1 Genetic Invalidation Thus Improved Heart Function Andmentioning
confidence: 99%
“…A bolus of 5 mg/kg (in 60 mL) was intravenously delivered over 30 min, then a 1 mg/kg per hour (15 mL/h) infusion was started and lasted throughout the study period. This dosage was derived from previous experiments performed in rodents (22). Importantly, the intensivist in charge of the animal was blinded for the given treatment, which was prepared by an independent investigator.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The mechanism by which LR12 inhibits TREM-1 signaling derives from its ability to bind to the TREM-1 ligand (22). We further demonstrated that these same peptide also modulates in vivo the inflammatory cascade triggered by infection, thus inhibiting hyperresponsiveness, organ damage, and death during sepsis in mice (22).…”
mentioning
confidence: 90%
“…In general, expression of TREM-1 is upregulated through stimulation with TLR agonists and cytokines [9]. Endogenous ligands for TREM-1 have been observed on PMN and platelets as well as in the sera of septic patients [10,11,12,13]. However, the exact nature of the TREM-1 ligand and cell-specific function of the TREM-1 receptor have so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%